Meningkatkan Jumlah Konsumen Melalui Media Sosial Instagram JRNY Coffee And Records Yogyakarta Sebagai Komunikasi Pemasaran - Putri, Ivana; Suryasuciramdhan, Arfian; Zulfikar, Meiby; Fitriani, Andini Restu; Aprilia, Sisca Dwi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The rapid development of technology has introduced social media to support marketing activities and make business easier. Instagram has great potential for promoting a business. It will be easier for the public to find out information about a business through information that is spread on social media. One business actor who uses Instagram as an online promotional medium is JRNY Coffee and Records. This research aims to find out how to increase the number of consumers through the JRNY Coffee and Records Instagram media as marketing communication. The marketing communication strategy used by JRNY Coffee and Records uses social media marketing theory through Instagram, which includes online communities, sharing of content, credibility, interaction and accessibility. This type of research also uses qualitative methods by analyzing or observing social media accounts. With the results, getting content uploaded on Instagram, as well as the facilities offered, are not boring. And it shows that promotional activities on Instagram are able to create an increase in the number of consumers.